Molecular Dynamics Analysis of Thermostable DNA Pol I ITB-1 - CHANGI WONG; PETER PROKSCH; LEE TUNG TAN; SAMUEL LIHAN; AAZANI MUJAHID; MORITZ MÜLLER (Microbiology Indonesia, 2007)
One of the thermostable enzymes, which has been widely used in the biotechnological research, is DNA polymerase. The coding sequence of local DNA Pol I gene from a local thermophilic bacterium, namely DNA Pol I ITB-1, has been cloned, sequenced, and overexpressed. However, study on thermostability of this enzyme is very limited. In the present study, thermostability of the protein was evaluated by thermal unfolding simulation at 300, 400, and 500 K. Our simulation revealed that the secondary and tertiary structures of the protein was not significantly affected by thermal perturbation at 300 K, but they were affected and even gradually unfolded by that perturbation at 400 and 500 K. Evaluation of the root mean square fluctuation (RMSF) of individual residues from the simulation at 400 and 500 K revealed the distribution of the thermostability regions in the protein structure. From the RMSF analysis at 400 K, we found that thermostability of the 3’-5’ exonuclease domain was lower compared to that of the other domains. Where as from the RMSF analysis at 500 K, we found that in each domain of DNA pol I ITB-1 there was a single extraordinary thermostable a-helix which was likely to be the core of each corresponding domain. Thus our simulation provides a thermostability map of DNA Pol I ITB-1. Such information will be very valuable for the next genetic engineering work in determining a mutation target to modify thermostability of this enzyme.